Talent Management and Organizational Innovation: The Role of Knowledge Sharing - Mirwanti Syunikitta; Ming Pong; Ton Kiat (Journal Markcount Finance, 2025)
In the era of knowledge-driven economies, talent management and organizational innovation have become critical for sustaining competitive advantage. Knowledge sharing is increasingly recognized as a key mechanism through which talent management practices foster innovation. However, the interplay between talent management, knowledge sharing, and organizational innovation remains underexplored, particularly in dynamic and competitive business environments. This study aims to investigate the role of knowledge sharing in mediating the relationship between talent management and organizational innovation, providing insights into how organizations can leverage talent to drive innovation. A quantitative research design was employed, utilizing survey data collected from 300 employees across various industries. Structural equation modeling (SEM) was used to analyze the relationships between talent management, knowledge sharing, and organizational innovation. The findings reveal that talent management significantly enhances organizational innovation, with knowledge sharing acting as a key mediator. Employees who actively participate in knowledge-sharing activities reported higher levels of innovation. Talent management practices, such as talent development and retention, were found to positively influence knowledge sharing, which in turn drives innovation. This study highlights the importance of integrating talent management with knowledge-sharing initiatives to foster organizational innovation.